Effort and Performance in Public-Policy Contests - Gil S. Epstein; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2002)
Government intervention often gives rise to contests in which the possible prizes' are determined by the existing status-quo and some new public- policy proposal . In this paper we study the general class of such two-player public-policy contests and examine the effect of a change in the proposed policy, a change that may affect the payoffs of the two contestants, on their effort and performance. We extend the existing comparative statics studies that focus on the effect of changes either in the value of the prize in symmetric contests or in one of the contestants' valuation of the prize in asymmetric contests. Our results hinge on the relationship between the strategic own-stake ( income ) effect and the strategic rival's-stake ( substitution ) effect. This relationship is determined by three types of ability and stakes asymmetry between the contestants. In particular, we specify the asymmetry condition under which a more restrained government intervention that reduces the contestants' prizes has the perverse effect of increasing their aggregate lobbying efforts.
Keywords: 330; public-policy contests; policy reforms; lobbying efforts; strategic own-stake effect; strategic rival's-stake ( substitution ) effect.